Comparison of Vitamin C, Î²-Carotene, and Water Content from Tamarillo (Solanum betaceum Cav.) Fruit and Tamarillo Jam - Zaidar, Emma (Journal of Chemical Natural Resources, 2020)
A research on the comparative analysis of levels of vitamin C, Î²-carotene, and water content, from a tamarillo fruit and its jam. Analysis of levels of vitamin C is done by the iodometric titration method, the analysis of levels of Î²-carotene performed by UV-VIS spectrophotometry, and water content analysis performed by the method of thermogravimetry. The research, found that levels of the vitamin C from tamarillo fruit were 12,3 mL/g and its jams is 6,16 mL/g, levels of Î²-carotene from the fruit is 180.91 ppm and its jam is 136.52 ppm, and water content of the fruit is 88.92% and its jams were 46.96%.